Tryptophan, an important link in regulating the complex network of skin immunology response in atopic dermatitis - Huang, Yaxin; Chen, Lingna; Liu, Fuming; Xiong, Xia; Ouyang, Yongliang; Deng, Yongqiong (Frontiers in Immunology, 2024)
Atopic dermatitis (AD) is a common chronic relapsing inflammatory skin disease, of which the pathogenesis is a complex interplay between genetics and environment. Although the exact mechanisms of the disease pathogenesis remain unclear, the immune dysregulation primarily involving the Th2 inflammatory pathway and accompanied with an imbalance of multiple immune cells is considered as one of the critical etiologies of AD. Tryptophan metabolism has long been firmly established as a key regulator of immune cells and then affect the occurrence and development of many immune and inflammatory diseases. But the relationship between tryptophan metabolism and the pathogenesis of AD has not been profoundly discussed throughout the literatures. Therefore, this review is conducted to discuss the relationship between tryptophan metabolism and the complex network of skin inflammatory response in AD, which is important to elucidate its complex pathophysiological mechanisms, and then lead to the development of new therapeutic strategies and drugs for the treatment of this frequently relapsing disease.